Emerging role of miRNAs in renal fibrosis. Issue 1 (2nd January 2020) - Fan, Youling; Chen, Hongtao; Huang, Zhenxing; Zheng, Hong; Zhou, Jun
ABSTRACT: As one type of the most common endogenous short noncoding RNAs (ncRNAs), microRNAs (miRNAs) act as posttranscriptional regulators of gene expression and have great potential biological functions in the physiological and pathological processes of various diseases. The role of miRNAs in renal fibrosis has also attracted great attention in the previous 20 years, and new therapeutic strategies targeting miRNAs appear to be promising. Some researchers have previously reviewed the roles of miRNA in renal fibrosis disease, but numerous studies have emerged over the recent 5 years. It is necessary to update and summarize research progress in miRNAs in renal fibrosis. Thus, in this review, we summarize progress in miRNA-mediated renal fibrosis over the last 5 years and evaluate the biological functions of some miRNAs in different stages of renal fibrosis. Furthermore, we also expound the recent clinical applications of these miRNAs to provide new insights into the treatment of renal fibrosis disease.